Developing and Validating a Clinical Warfarin Dose‐Initiation Model for Black‐African Patients in South Africa and Uganda. Issue 6 (28th December 2020) - Asiimwe, Innocent G.; Waitt, Catriona; Sekaggya‐Wiltshire, Christine; Hutchinson, Claire; Okello, Emmy; Zhang, Eunice J.; Semakula, Jerome R.; Mouton, Johannes P.; Cohen, Karen; Blockman, Marc; Lamorde, Mohammed; Jorgensen, Andrea L.; et al.
Abstract : Warfarin remains the oral anticoagulant of choice in sub‐Saharan Africa. However, dosing is challenging due to a highly variable clinical response for a given dose. This study aimed to develop and validate a clinical warfarin dose‐initiation model in sub‐Saharan Black‐African patients. For the development cohort, we used data from 364 patients who were recruited from 8 outpatient clinics and hospital departments in Uganda and South Africa (June 2018–July 2019). Validation was undertaken using the International Warfarin Pharmacogenetics Consortium (IWPC) dataset (690 black patients). Four predictors (age, weight, target International Normalized Ratio range, and HIV status) were included in the final model, which achieved mean absolute errors (MAEs; mean of absolute differences between true dose and dose predicted by the model) of 11.6 (95% confidence interval (CI) 10.4–12.8) and 12.5 (95% CI 11.6–13.4) mg/week in the development and validation cohorts, respectively. Two other clinical models, IWPC and Gage, respectively, obtained MAEs of 12.5 (95% CI 11.3–13.7) and 12.7 (95% CI 11.5–13.8) mg/week in the development cohort, and 12.1 (95% CI 11.2–13.0) and 12.2 (95% CI 11.4–13.1) mg/week in the validation cohort. Compared with fixed dose‐initiation, our model decreased the percentage of patients at high risk of suboptimal anticoagulation by 7.5% (1.5–13.7%) and 11.9% (7.1–16.8%) in the development and validation cohorts, respectively. The clinical utility of this model will be tested in a prospective study. Study Highlights WHAT IS THE CURRENT KNOWLEDGE ON THE TOPIC? ☑ Warfarin dosing remains challenging due to a highly variable clinical response for a given dose. WHAT QUESTION DID THIS STUDY ADDRESS? ☑ Can a clinical dose‐initiation model be developed and validated for sub‐Saharan Black‐African patients? WHAT DOES THIS STUDY ADD TO OUR KNOWLEDGE? ☑ We have developed the first warfarin dose‐initiation clinical model for Black‐African patients in Uganda and South Africa. HOW MIGHT THIS CHANGE CLINICAL PHARMACOLOGY OR TRANSLATIONAL SCIENCE? ☑ We will be implementing and validating this model in a prospective cohort to inform future large‐scale implementation. More optimized dosing should improve the quality of warfarin anticoagulation in these two developing countries.